Multi-institutional evaluation comparing guidance from International Ki67 Working Group vs National Health Commission of China on immunohistochemistry-based Ki67 assessment alongside the Quantitative Dot Blot method - Wang, Yin; Zou, Jiarui; Cao, Qinghua; Dai, Guihong; Fan, Panhong; Gong, Xue; Jiang, Jinyan; Kong, Yanqing; Liu, Chao; Liu, Chunhui; Lu, Chenjia; Li, Meiren; et al. (Frontiers in Oncology, 2025)
PurposeRecommendations from the National Health Commission of China (NHCC) and the International Ki67 Working Group (IKWG) were issued to guide immunohistochemistry (IHC)-based Ki67 scoring for breast cancer patients in daily clinical practice. They were evaluated in this multi-institutional study alongside the results from the Quantitative Dot Blot (QDB) method.MethodsThree alternative adjacent sections from 40 primary ER+ breast cancer resection blocks were randomly assigned a number from 1 to 120 for Ki67 staining and reviewed by 21 pathologists, while the other three alternative sections were sent for QDB analysis of Ki67 protein levels. Ki67 scores were grouped by 5/30% (IKWG), 10/30% (NHCC) and 20/30% (NHCC appendix 9, NHCCa9), respectively while QDB results were grouped by C5–C95 of 2.31 nmol/g defined in previous study as low-, equivocal-, and high-risk groups.ResultsThe overall Intraclass Correlation Coefficient (ICC) was 0.785 for IHC evaluations from 21 pathologists, with Fleiss Kappa values of 0.555, 0.628, and 0.480 when Ki67 scores were grouped by guidance from IKWG, NHCC, and NHCCa9, respectively. In comparison, the ICC and Fleiss kappa values for the QDB analysis were 0.939 and 0.831, respectively. When IHC and QDB results were cross-referenced, more specimens were grouped as high-risk by QDB than IHC, and NHCCa9 led to the highest percentage of disagreement between the two methods.ConclusionThe IKWG recommendation was harder to achieve categorized agreement among pathologists than the NHCC recommendation, yet it led to the best agreement with the QDB to define the low-risk group. The QDB method offers significantly improved consistency compared to the current IHC-based Ki67 assessment.